The Principal’s Strategy in Improving Teachers’ Teaching Performance at RA Hidayatul Khoir Purwakarta - Enung Nurlaela (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the principal's strategy in improving teachers' teaching performance and the impact of this strategy at RA Hidayatul Khoir Purwakarta. The principal's leadership plays a central role in guiding and developing teacher professionalism. Optimal teacher performance significantly determines the quality of learning and the achievement of educational goals. This study employed a qualitative approach with a case study method. Data collection was conducted through observation, in-depth interviews with the principal and teachers, and documentation. Data analysis used the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. Data validity was tested through source triangulation and technique triangulation. The research findings indicate that the principal's strategies in improving teachers' teaching performance include: providing motivation through emotional and structural approaches, involving teachers in training and workshops to enhance competence, conducting regular supervision and evaluation, conducting benchmarking visits to more advanced schools, creating a conducive and comfortable work environment, providing rewards and recognition to high-performing teachers, and implementing participatory leadership by involving teachers in decision-making. The impact of these strategies includes increased teacher work motivation, teacher professionalism in teaching, students' academic and non-academic achievements, and the creation of a positive work culture in the school. The principal also provides direct role modeling by actively filling in for absent teachers and being present daily to manage the school. This research concludes that participatory, motivational, and exemplary leadership strategies of school principals are highly effective in improving teachers' teaching performance.